Thinking Statively and Dynamically: A View from Georgian - Bondarenko, Tatiana; Luo, Richard; Rouillard, Vincent (Proceedings of the Amsterdam Colloquium, 2024)
Whether verbs like think can embed questions depends on lexical aspect (Özyıldız 2021; Özyıldız 2024): stative ‘think’ is compatible only with declarative complements, whereas process ‘think’ can combine with both declaratives and interrogatives. In this paper we provide a refinement to this generalization based on the data from Georgian, and propose an account of why such dependence between lexical aspect and embeddability of questions holds. We propose that both stative and process ‘think’ are derived from a more abstract common core—the former via a genericity operator (Özyıldız 2024), the latter via a cumulativity operator—and argue that the genericity operator leads to interpreting ‘think’ as ‘believe’ with declaratives, but gives rise to a semantically deviant meaning with interrogatives.